Perencanaan pembangunan kehutanan daerah dalam perspektif good governance - Khuswantoro Akhadi; Andy Fefta Wijaya; Imam Hardjanto (Foresty Faculty of Hasanuddin University, 2013)
Sustainable use of forest resources is needed to establish a forestry management plan. Forest management plans exist at the provincial level according to the conditions and problems. Forestry planning at Provincial level depicts current forest conditions, institutional conditions, the contribution of economy, social and ecology associated with the provincial level strategic issues. This paper tries to elaborate the local development planning of forestry from good governance perspective, and role of stakeholders of local development forest planning. The research was based on qualitative descriptive approach to the study site in the province of Yogyakarta and West Papua. The result shows that forest planning in the region is top-down with respect to existing regional characteristics. To realize the principles of good governance, a gap for each stakeholder role in the arrangement, implementation, monitoring and evaluation to reporting should be made. The role of government in the area of forestry development planning in terms of good governance, the rule of law for the regulation in the forestry sector has been completed. Partnership is the key word synergy in the implementation of good governance in forestry development in the area will attention to the aspects of partnership and equity between all stakeholders in the arrangement, implementation, monitoring and evaluation and reporting of forest development.